Interactive theorem proving : 7th International Conference, ITP 2016, Nancy, France, August 22-25, 2016. Proceedings /: 7th International Conference, ITP 2016, Nancy, France, August 22-25, 2016. Proceedings. (2016) - Unknown
No abstract available